(untitled) (Global Journal of Computer Science and Technology, 2017)
A novel non-chaos based digital image encryption technique using a combination of diffusion and substitution process has been presented. A secret key of 128 bit sizes is used in the algorithm. In the diffusion (permutation) method, image is divided into different dynamic blocks which are key dependent. Further, each block is made to pass through eight rounds of permutation process. In this process, a zigzag mechanism is used to scramble the block pixels within the block. Then the resultant image i.e. the partially encrypted image is divided into various key based dynamic sub-images. Pixels of the sub-images are replaced with another pixel values within the block when each of the sub-images are passed through the substitution process. The substitution process comprises of four rounds. The proposed scheme is then compared with the standard AES algorithm. Investigation outcome shows that the proposed design methodology is efficient, fast and secure